The effect of sodium phosphate supplementation on appetite and energy intake in trained individuals - Guelfi, K. J.; West, J. S.; Ayton, T.; Wallman, K. E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Ingestion of an acute dose of phosphate has been shown to attenuate energy intake in the subsequent meal (Obied et al., 2010). This raises the question of whether the practice of phosphate supplementation over a number of days by athletes to enhance performance also influences appetite and energy intake. The aim of this study was to investigate the effect of 6 days of phosphate supplementation on appetite and energy intake in trained individuals. This may have implications for athletes that frequently supplement with sodium phosphate to ensure that energy intake is sufficient to support optimal exercise performance. A secondary aim was to confirm the previously observed benefits of sodium phosphate supplementation for aerobic capacity. Methods: Twenty moderately trained individuals participated in two, 6 day phases of supplementation with either sodium phosphate (50 mg/kg of fat free mass per day) or a placebo, in a double-blinded, counterbalanced design. To assess the effect of supplementation on energy intake, a laboratory breakfast meal was provided on days 1, 2 and 6 of supplementation from which ad libitum energy intake was determined. Energy intake from all other food and drink intake during each supplementation period was determined from self-recorded food diaries. Following the 6 days of supplementation, peak aerobic capacity was assessed. A 2-3 week wash-out was imposed between supplementation phases. Results: There was no significant effect of an acute dose of sodium phosphate on energy intake or perception of appetite (hunger, fullness, desire to eat or prospective food consumption) at the initial laboratory breakfast meal (i.e. day 1 of supplementation; p > 0.05). Likewise, there was no effect of supplementation on energy intake or perception of appetite at the laboratory breakfast meal on day 2 or day 6 of supplementation (p > 0.05). There was also no effect of supplementation on daily energy intake from the self-recorded food diaries (p > 0.05). With respect to the effect of supplementation on peak aerobic capacity, there was no difference between trials (p > 0.05). Discussion: In summary, 6 days of sodium phosphate supplementation does not appear to influence energy intake. Therefore athletes supplementing with sodium phosphate can do so without hindering nutritional status. However, given that phosphate supplementation failed to improve aerobic capacity, the ergogenic benefit of this supplement remains questionable.